Educational policy and management strategies in the development of digital skills and media competencies in teacher training: New approaches to education - Andrey V. Sazonov; Milana E. Kuprianova (RUDN Journal of Public Administration)
The study analyzes the need to integrate digital skills and media competencies into the process of teacher training. It has been found that modern educational programs often do not meet the requirements of the digital era, necessitating their updating and the introduction of courses on digital literacy. The results highlight the importance of continuous professional development for teachers and the adaptation of educational standards to rapidly changing technological conditions.